HEREDITARY OSTEOPETROSIS OF THE RABBIT : II. X-RAY, HEMATOLOGIC, AND CHEMICAL OBSERVATIONS - Pearce, Louise (The Rockefeller University Press, 1948)
The results of x-ray, hematologic, and chemical studies on cases of hereditary osteopetrosis of the rabbit are described and the resemblance of the findings to those of the severe juvenile form of human osteopetrosis is pointed out. The outstanding feature of the x-ray examinations was the homogeneous dense appearance of the entire skeleton. This condition was present at birth. In older cases there was evidence of some differentiation of bone structure. The hematologic studies showed that the disease was characterized by the development of a macrocytic anemia, thrombocytopenia, and a moderate myeloid leucocytosis. Other abnormal findings included high reticulocyte and normoblast counts, anisocytosis and poikllocytosis, and degenerative changes of the neutrophiles and lymphocytes. The chemical studies showed very low serum calcium values; serum phosphorus values were low during the first 4 weeks of life but were somewhat higher than normal levels in older cases. The serum phosphatase values were elevated. The blood sugar content was generally low. The blood cholesterol values were generally high. The liver glycogen values were small especially in older cases and those for muscle glycogen were somewhat smaller than normal values.